PEMETAAN KOMODITAS SAYUR UNGGULAN DI PROVINSI LAMPUNG - Edy Humaidi; Bina Unteawati; Analianasari Analianasari (Jurnal Agribisnis Indonesia, 2020)
This study aims to map the types of vegetables that are feasible to be developed in Lampung Province. The mapping will be analyzed using the Location Quotient (LQ) method which will produce commodities that are classified as either base or non-base commodities. The data used are secondary data on vegetable production in Lampung Province for six years (2013-2018) obtained from the Central Statistics Agency of Lampung Province. The results showed that two types of vegetable plants became superior commodities, seen from the LQ value greater than 1, namely chilli and Chinese cabbage, with an LQ value of 1,26 for chilli and 1,17 for Chinese cabbage, respectively.